The Hidden Burden of Toxic Positivity: A Systematic Review of Emotional and Organizational Impacts - Abdul Rahman Ibrahim (PSYCHONESIA: JOURNAL OF PSYCHOLOGY, 2025)
This study systematically examines the concept of toxic positivity, a condition in which excessive optimism suppresses emotional authenticity and undermines psychological well-being. Using a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework, eight peer-reviewed studies published between 2020 and 2024 were analyzed. Data were collected from Scopus, Google Scholar, ScienceDirect, and Taylor & Francis Online, and assessed through the Critical Appraisal Skills Programme (CASP) checklist. Thematic synthesis identified three dominant patterns: emotional suppression as a maladaptive coping mechanism, digital culture reinforcing the “happiness imperative,” and workplace norms promoting emotional labor and burnout. The findings demonstrate that toxic positivity functions as a socially reinforced emotional bias that negatively affects mental health and organizational well-being. This review emphasizes the need for balanced emotional expression and offers practical insights for developing psychologically sustainable environments in both digital and occupational contexts.